Letter - Dalmau, Francisco
030-0039-001 OFICINAS: CORTES, 615 TELEFONO 10000 TELEFONEMAS) TELEGRAMAS) EXIM CABLEGRAMAS) CODE: A.B.C. 5.th EDITION FRANCISCO DALMAU BARCELONA, 11th, Sepbre, 1938 Apartado N.o 2 To the Secretary General Trade Unions London. Dear Sir ; I will like to make a present of 1000 tons of milk powder, for our infancy, that suffer mostly of the war. The help of english Trade Unions, can be very valuable to me.- England enjoy the Christmas family festivities and for that purposse I will send round 1,320,000, bottles, of old tawny Pilatus, a wine that has the favour of the british taste. We can sell in London at the rate of 2/6 a botlle, first class quality and vintage wine. The bottling will be done by english workers.- H, M, Customs and Excise will get large amounts of Customs, about 70000 pounds. The difference will be to buy the milk. If you are capable to engage your Trade Unions to take 1,320,000 bottles of vintage wine at 2/6, they will help our infancy and get value for his money.- If you like to sell a bottle to every of your members, then the present of milk can be increased several times and I am dispossed to give the necessary to developp this proposal. Hoping of your kind attention and thanking you in advance, I am, dear Sir, Yours faithfully F Dalmau 165,000 70,000 £95,000 292/946/30/39